La justice, un patrimoine muséal méconnu, l’exemple du musée de Bretagne - Laurence Prod’homme (In Situ)
If we take the word justice to mean the men and women who practise it, those who endure its decisions and even the places where it is exercised, then it is that multi-dimensional idea which can be observed in the Museum of Brittany’s collections from the 17th century to today.The first collection which comes to mind is that which was started in 1899 around the famous Dreyfus Affair and more precisely the trial which took place in Rennes. This collection currently consists of more than 7.000 items including letters, original photographs, postcards and posters. The museum recently acquired thirteen volumes to enrich its collection, put together by Félix Froissart, the public prosecutor at the time; they will be the object of extensive research via a Master’s in History supported by a grant.If we go back further into the history of the town and the region, the collection has items linked to the Breton Parliament: etchings, drawings, photographs, petty bags, portraits of political figures, rubber stamps and seals. Different popular images illustrate several sensational cases in the museum’s collections. One such case is that of Hélène Jégado whose funeral mask is in the vaults. Buildings linked to the theme of justice are represented with plans and original 19th century photos, like those of the women’s prisons in Rennes or the jail in Brest where forced labour was endured.The collections also bear witness to modern history with items linked to the association of voluntary fighters of the Resistance movement and a series of posters from different separatist movements.These extensive collections come with an added premium: they are all freely accessible via the museum’s online collection.